2020
DOI: 10.1111/eve.13262
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils of the horse: Part II: Eosinophils in clinical diseases

Abstract: Interpretation of eosinophilia in body fluids or tissues is often not straightforward. Eosinophil counts vary among clinically healthy individuals, and considerable overlap can occur between normal and affected animals in conditions such as allergic airway disease. Parasite exposure is a confounding factor when counts are increased, and in cases where very high counts and dramatic clinical signs make another disease process obvious, the underlying pathology may be uncertain and treatment difficult. Eosinophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 206 publications
(302 reference statements)
0
9
0
Order By: Relevance
“…With regard to the recent review on eosinophils in clinical diseases in horses ("Eosinophils of the horse: Part II: Eosinophils in clinical diseases") (Brosnahan, 2020), we would like to highlight some errant omissions in the article particularly in the part about insect bite hypersensitivity (IBH) in horses.…”
Section: Dear Editormentioning
confidence: 99%
“…With regard to the recent review on eosinophils in clinical diseases in horses ("Eosinophils of the horse: Part II: Eosinophils in clinical diseases") (Brosnahan, 2020), we would like to highlight some errant omissions in the article particularly in the part about insect bite hypersensitivity (IBH) in horses.…”
Section: Dear Editormentioning
confidence: 99%
“…Previous studies have shown that cytokine-or leukocyterelated gene expression in the blood can effectively reflect the host immune response in horses (18)(19)(20)(21)(22). But most of the studies on associations between parasite infections and immune responses in equine animals have mainly studied parasite antigen-induced host antibodies (23)(24)(25), and immune cells (26), clinical signs (27-30), and pathophysiology (31) in the host. It is our knowledge that only one study has evaluated gene expression in the whole blood of domestic horses infected with cyathostomin parasites (32).…”
Section: Introductionmentioning
confidence: 99%
“…
Thank you for providing the opportunity to respond to comments from Drs. Birkmann and Fettelschoss-Gabriel submitted in reference to 'Eosinophils of the horse: Part II: Eosinophils in clinical diseases' (Brosnahan, 2020a(Brosnahan, , 2020b.The authors begin by noting that the pathogenesis of insect bite hypersensitivity (IBH) in horses may also involve a type IVb hypersensitivity reaction. They further present newer data from their research group that demonstrated a clear increase in both localised and peripheral blood eosinophils, and a correlation of peripheral blood eosinophils with severity of disease.
…”
mentioning
confidence: 99%
“…Thank you for providing the opportunity to respond to comments from Drs. Birkmann and Fettelschoss-Gabriel submitted in reference to 'Eosinophils of the horse: Part II: Eosinophils in clinical diseases' (Brosnahan, 2020a(Brosnahan, , 2020b.…”
mentioning
confidence: 99%